(3GdeTcGg GdRLGLjI HTQM GdefXheI GdSQGLjIs - (3LeGd GdOjf eMeO Hf YHO GdQMef Hf SQGL GdOjf HGLeGd GdMVQejs ((3YHO Gddg Hf YeQ Hf eMeO Hf YHhO HTjQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CMd dYHGOg GdWjHGJ hHYO , abO bGd Udi Gddg Ydjg hSde (B: (3GdfcGM SfJi aef QZH Yf SfJi adjS efi , hgh SfI GdCfHjGA hTYGQ GdChdjGA s
(3BNQgG (B:s
(3aEf QCi GdMGce Cf dGJaQjW hdG Ndd efgG de JHWd hdG HJgG , hEdG HWdJ Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3cJH eJf GdefXheI HGdMeQIs
(3Ydi ghGeT GdfSNI JYdjbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs